Boron and orthopedic implants: A review of the literature - Emin Özkul; Recep Tekin; Sait Anıl Ulus; Ramazan Atiç; Şeyhmus Yiğit; Mehmet Sait Akar; Fatih Durgut; Sait Dönmez (Chakra Brahmanda Lentera Institute, 2022)
A material created to interact with biological systems to enhance, treat or modify a tissue, organ, or body function is called a biomaterial. Sutures, dental fillings, needles, catheters, bone plates, and orthopedic implants are the most commonly used medical biomaterials. With the increasing use of orthopedic implants worldwide, there remains significant interest in developing new technologies to improve the effective clinical performance of contemporary treatment modalities and devices. Biomaterials used in orthopedics often require revision due to problems such as wear, corrosion, and infection. These revisions have become a significant burden for the patient and the healthcare system. Boron, with its unique properties, is an element that has the potential to overcome these problems. Therefore, in recent years, the importance of boron elements in the health field as well as in the industrial field has been noticed, making the use of boron in medicine very popular